Characteristics of Islamic Religious Education in Factory Employee Families (Case Study of Children Aged 6-17 Years in Factory Employee Families in Purwakarta District, West Java) - Cucu Komariah; Mahmud Mahmud; Hariman Surya Siregar; Dewi Sadiah (Journal of General Education and Humanities, 2026)
The family serves as the primary environment for shaping children’s personality, morality, and religious character. However, in industrial communities, particularly among factory worker families, implementing Islamic Religious Education (IRE) often encounters challenges due to limited parental time, shift work, and economic pressures. This study aims to describe the characteristics of Islamic Religious Education in factory worker families, focusing on parenting patterns, educational implementation, and the religious values instilled in children aged 6–17 years. The study employed a qualitative case study approach. The research participants consisted of factory worker families with children aged 6–17 years in Purwakarta District, West Java. Data were collected through in-depth interviews, observations, and documentation to obtain a comprehensive understanding of Islamic religious education practices within the family setting. The findings reveal that Islamic Religious Education is implemented through the habituation of worship practices, parental role modeling, and simple, contextual religious communication. Despite facing time constraints and demanding work conditions, parents continue to play an active role in fostering children’s religious development by instilling values of faith, morality, discipline, responsibility, and respect. These practices help maintain the continuity of religious education within factory worker families and support the development of children’s Islamic character.